Effect of polar groups in lubricants on sliding speed dependent friction coefficients of DLC coatings. (6th March 2015) - Yoshida, K.; Kano, M.; Masuko, M.
Abstract : The speed dependent friction coefficients of two types of DLC coatings, a-C:H and ta-C, were evaluated when lubricated with 1-hexadecene, which did not contain any functional group, and with oleic acid and oleyl alcohol that did. The friction coefficient measured for ta-C at a low sliding speed of 0·01 mm s −1 with the 1-hexadecene lubricant that did not contain any functional group was 0·22, which was higher than the value of 0·11 seen for a-C:H. The friction coefficients measured for a-C:H and ta-C at a high sliding speed of 50 mm s −1 with 1-hexadecene were 0·10 and 0·06 respectively. The friction coefficients measured with oleic acid and oleyl alcohol were 0·02 for a-C:H and less than 0·001 for ta-C. The results showed that the friction coefficient of ta-C was more strongly influenced by the functional group in the lubricants than that of a-C:H. It is assumed that this difference between the two coatings can be attributed to a difference in the capability to form a tribochemical reacted film under boundary lubrication. Under mixed lubrication, differences in lubricity also affected this friction coefficient difference, in addition to the properties of the tribochemical reacted film.